COVID-19 lockdown: impact on online gambling, online shopping, web navigation and online pornography - Lorenzo Zamboni; Silvia Carli; Belleri Marika; Rosaria Giordano; Giulia Saretta; Fabio Lugoboni (SAGE Publishing, 2021)
Background: The COVID-19 pandemic and control measures may have had an impact on unpleasant emotions experimented during the lockdown (LD). This may have increased the number of hours spent online and could have impacted the quality of the enacted behavior, in terms of loss of control of Internet use. In this online survey, we were interested in measure how much loss of control was perceived regarding online gambling, online shopping, the fruition of online pornographic content and web navigation. Design and methods: The online survey was carried out during the COVID-19 pandemic in the post-lockdown and 1232 subjects participated in the survey. In the participating sample, healthcare workers (HW) were 43.1% of the sample, of which 18.7% were directly involved in the Coronavirus emergency, and 52.3% of the sample is not a HW. Only 0.6% of the sample gambled online and 37.5% of those reported losing control of their gambling mode. Most of the sample shopped online during the LD (70.1%), but only 7.2% of those lost control by buying and/or spending more than what they had set themselves. Results: Significant data emerged showing that those who lost control while online shopping also lost control regarding the amount of time spent online (p<0.001); 21.6% of the sample, reported making use of online pornographic material during LD, 4.7% of them stated that the frequency increased and 5.1% reported losing control by having spent more money or more time than what was intended. Finally, 44.7% of the sample have experienced loss of control during the web navigation. Furthermore, during the LD 67.8% of the sample reports having experienced unpleasant emotions. Of these, 8.4% state that they enacted behaviors such as online gambling, online shopping, online pornographic material viewing and web navigation to counter their negative emotions. Interestingly, we found a correlation between loss of control during web navigation and online shopping and the emotional states "upset", "scared" and "restless" (p<0.05). Conclusion: To conclude, there was no significant increase in potentially addictive behaviors, nor an increase in loss of control of these behaviors when enacted online. However, the loss of control in online shopping and web navigation was significantly correlated to the unpleasant emotional states of nervousness, fear and restlessness, whereas those who reported feeling strong and able to handle the situation experienced a lower loss of control in their web navigation. These correlations may suggest that these online behaviors may act as modulators of unpleasant emotional states.